Hashimoto’s Thyroiditis Can Occur Not Only in The Adolescence Period But also in Children Under Five Years of Age - Amine Aktar Karakaya; Edip Ünal; Aslı Beştaş; Fatma Özyalın (Güncel Pediatri)
Introduction: Hashimoto’s thyroiditis (HT) is one of the most common autoimmune endocrine disorders in the pediatric age group. In this study, it was aimed to retrospectively examine our cases, who were children and adolescents diagnosed with HT. Materials and Methods: We retrospectively examined 119 patients between the ages of 1 and 18, who were diagnosed with HT. In all of the cases, physical examination findings, thyroid function tests, anti-thyroid peroxidase (anti-TPO) and antithyroglobulin (Anti-Tg) antibodies, thyroid ultrasonographies and accompanying autoimmune diseases were evaluated. Results: The female/male ratio was 3.5/1. In our cases, the median age at the time of diagnosis was 12.29 years and 10 (8.4%) of the cases were under the age of five. At the time of diagnosis, 37% of the cases were euthyroid, 21.8% had overt hypothyroidism, 34.5% had subclinical hypothyroidism, 2.5% had subclinical hyperthyroidism and 4.2% had overt hyperthyroidism. At the time of diagnosis, 102 cases (85.7%) had anti-TPO and 82 cases (68.9%) had anti-Tg positivity. The Anti-TPO levels at the time of admission were found to be significantly higher in the hypothyroid group compared to the euthyroid group. Conclusion: Thyroid function test results of patients with Hashimoto’s thyroiditis may vary in the follow-up period. Even though most cases with euthyroidism remain euthyroid, some might progress to hypothyroidism. Although Hashimoto’s thyroiditis is most frequently seen in adolescents, approximately 10% of the cases are under the age of five. Therefore, autoimmune thyroiditis should be considered in hypothyroidism occurring in the early stages of life.